Komunikasi Simbolik Masjid Agung Keraton Buton - La Ode Jumaidin (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT The title of this study is the Communication Symbolic of Grand Mosque Buton palace reveal existence an dexpression collective Integrative Awareness in Buton Community Social systems. This study aims to reveal the symbolic form of communication and trying to understand the link ages and symbolic communication Ahmadiyah mosqu eon the expression of the collective consciousness in the social system of integrativeculturalSociety of Buton. The method of the research is in its implementation apply multi dimensional approach. The poin the stressedis not just one approach toscience alone, but seeks to unravel the phenomenon of symbolic communication integrity in the Great Mosque of Sultan Buton primarily phenomenological approach and ethnographic approaches. This study in cludes the type of qualitative research-emphasizing descriptive observational participatory, in-depth interviews and documentation. Mosque of Sultan Buton is the only relic of the Government of the Sultanate of Buton remaining and still exists and functions today. Work for the Buton mosque is not just an artifact of communication, but as a complex symbol that communicates therhythmand momentum of the movement of history, comparative advantage, productivity, and creativity, the ability to transform great ideas in the context of local socio-cultural, cognitive intelligence, emotive, behavioral, and spiritual depth of intelligence achievement. Key words: communication symbolic, multidimensional approach, grand mosque of Buton palace